2007
DOI: 10.1097/01.ede.0000249425.32990.b9
|View full text |Cite
|
Sign up to set email alerts
|

Water Quality Indicators and the Risk of Illness at Beaches With Nonpoint Sources of Fecal Contamination

Abstract: Traditional fecal indicators currently used to monitor these beaches were not associated with health risks. These results suggest a need for alternative indicators of water quality where nonpoint sources are dominant fecal contributors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
262
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 318 publications
(268 citation statements)
references
References 27 publications
3
262
1
2
Order By: Relevance
“…Recent waterbody closures at Brazilian Olympic venues 4 and Waikiki beach, Hawaii 5 illustrate recreational water contamination's public health and economic reach. Several cohort studies and randomized trials have measured swimming-related health risks and risks associated with exposure to waters containing elevated fecal indicator bacteria levels, [6][7][8][9][10][11][12][13][14][15][16][17] but individual studies are usually too small to estimate the public health burden associated with water exposure with respect to missed daily activities (work, school, vacation) or medical visits and hospitalizations that result from gastroenteritis. Moreover, individual studies have not typically enrolled enough swimmers to estimate risks separately for children.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent waterbody closures at Brazilian Olympic venues 4 and Waikiki beach, Hawaii 5 illustrate recreational water contamination's public health and economic reach. Several cohort studies and randomized trials have measured swimming-related health risks and risks associated with exposure to waters containing elevated fecal indicator bacteria levels, [6][7][8][9][10][11][12][13][14][15][16][17] but individual studies are usually too small to estimate the public health burden associated with water exposure with respect to missed daily activities (work, school, vacation) or medical visits and hospitalizations that result from gastroenteritis. Moreover, individual studies have not typically enrolled enough swimmers to estimate risks separately for children.…”
mentioning
confidence: 99%
“…2,21 We conducted a pooled analysis of 13 prospective cohorts in the United States (84 411 participants). [7][8][9][10][11][12][13][14] We coordinated studies to ensure similar designs and measurement methods. This approach enabled us to calculate summary estimates for gastroenteritis risk and related medical and daily activity impacts associated with recreational water exposure and Enterococcus levels; it also enabled us to report for the first time, to our knowledge, separate estimates for children aged 0 to 4 and 5 to 10 years.…”
mentioning
confidence: 99%
“…from three coastal locations of Northern Ireland (27). Gulls can be major contributors of fecal contamination in recreational beaches, with loadings of up to 10 8 Escherichia coli bacteria per fecal dropping (1); however, in areas predominantly impacted by seagulls, the level of contamination appears to be unassociated with health risks (5). This suggests that many of the Campylobacter species contaminating beaches may not be infectious to humans.…”
mentioning
confidence: 99%
“…are in gull excreta. In particular, there are no published data for California gulls (Larus californicus), even though they are ubiquitous in western coastal areas of the United States and have been suspected to be an important source of fecal pollution for recreational beaches (5). Quantification of potentially human infectious Campylobacter spp.…”
mentioning
confidence: 99%
“…Studies have indicated that risk of gastrointestinal illness associated with exposure to recreational waters impacted by animal feces may not be different from waters impacted by human sources. Nonetheless, human health risk from exposure to recreational waters impacted by non-human sources is still not well understood; some studies did not find statistically significant associations between illness risk and fecal contamination of water by animal sources [17,18].…”
Section: Identify Potential Sources Of Fecal Contamination Of Recreatmentioning
confidence: 99%